Association of interleukin-1 α (-889) gene polymorphism in patients with generalized aggressive and chronic periodontitis - Komal Puri; Mehak Chhokra; Vidya Dodwad; Nikhil Puri (Wolters Kluwer Medknow Publications, 2015)
Background: There is a strong evidence that genetic as well as environmental factors affect the age of onset, severity and lifetime risk of developing periodontitis. The objective of the present study was to compare and to evaluate the association between interleukin (IL)-1α(-889) and gene polymorphisms in patients with generalized aggressive periodontitis, chronic periodontitis and healthy controls. Materials and Methods: A total of 60 Indian patients, with 20 aggressive periodontitis, 20 chronic periodontitis and 20 healthy controls were recruited for this study. From each patient, a volume of 2 ml of blood was collected by venipuncture in the ante-cubital fossa and was stored in sodium EDTA vacutainers and was used for genotyping assays with the polymerase chain reaction restriction fragment length polymorphism technique. Clinical parameters such as oral hygiene index, gingival index and clinical attachment loss (CAL) were evaluated for each patient. Genotype distribution between different groups were analyzed using Chi-square test. A P = 0.05 or less was set for significance. Results: The mean oral hygiene index was 3.7 ± 0.86 and 3.25 ± 0.30 for chronic and aggressive periodontitis cases respectively. The CAL was 4.29 ± 0.63 mm for chronic periodontitis and 6.44 ± 0.57 mm for aggressive periodontitis. Homozygous genotype 2,2 was more predominant in cases of aggressive periodontitis whereas in chronic periodontitis, heterozygous genotype 1,2 was more predominant when compared with others (P < 0.001). Odds ratio for aggressive versus chronic periodontitis was calculated as 6.2 (95% confidence interval 6.019-7.892). Conclusion: The results of the present study support a positive association between aggressive periodontitis and the presence of the IL-1α-889, allele 2 polymorphism in Indian patients.